(untitled) (Journal of Hama University, 2025)
The search aimed to determine the impact of some factors on preparation of the production and the formulation of agricultural policies in the Zabadani area in the rural Damascus Governorate. the research was carried out in some of the villages belonging to the administrative district (the Zabadani area) taken by the random sampling method and the number of them (24).and (27) guides and (78) farmers were selected by random sampling method from the mentioned villages. The objectives of the research were achieandved based on the application of the binary and multiple logistic regression model to determine the impact of a set of independent factors in the dependent variables (preparation of the agricultural production plan, participation in the formulation of agricultural policies, the degree of participation of extension units in the preparation of the production plan). the results of the analysis showed that one of the most important factors with a positive moral impact in the preparation of the agricultural production plan is to commit the unit to specific percentages of crops at a moral level of (1%), in the formulation of agricultural policies is to participate in the rationalization of water uses at a moral level of (1%), and in the degree of participation of the indicative units in the preparation of the production plan is to commit the unit to specific percentages of crops and flexibility in the preparation of the plan at a moral level of (1%).The research came up with a set of recommendations, such as emphasizing the participation of researchers in the adoption of the annual agricultural production plan ,participation in the formulation of agricultural policies ,and the adoption of the planning guideline